POPULASI CACING TANAH PADA BERBAGAI KUALITAS SERESAH (C, N, C/N, LIGNIN, DAN POLYPHENOL) (Studi kasus pada lahan Agroforestry di Taman Nasional Kelimutu, Kabupaten Ende) - Agustinus JP Ana Saga (AGRICA, 2017)
Population of the Earthworm on Various Litters Quality (C, N, C / N, Lignin, and Polyphenol) (Case study on Agroforestry Field in Kelimutu National Park, Ende Regency). This study aims to evaluate the population of earthworms and the quality of plant organic matter in various agroforestry systems, intensive agriculture and secondary forests. Taking samples of plant organic matter and earthworms conducted in January - July 2016 (in the rainy season) on the land Agroforestry : Clove (AF – CK), Cocoa (AF – KK), candlenut (AF – KM, cofee (AF – KP) compared to intensive farmland (monoculture vegetable crops) and secondary forest (SPL - HS), with 3 x replications. The observed variables in addition to the number of earthworms found and the monolith sampling, also observed the quality of plant organic matter (C (Walkley and black), N (Kjehldahl), Lignin, and Polyphenol (Goering and Van Soest)) (Kuadran). Survey results showed that the earthworm population in SPL-AF was as low as the population in SPL-HS, averaging 3 m - 2, while in SPL - PI averaged only 0.24 m -2. The earthworm biomass in AF is about 69% smaller than the worms found in SPL - HS; average earthworm biomass in SPL - AF 15 g m - 2 whereas in SPL - HS averaged 47 g m - 2; and the smallest worm biomass found in SPL-PI averaged about 2.3 g m-2. The average quality of organic matter of C - org plants in all SPL was 38% to 50%, the highest C - org levels of AF - CK, AF - KP and SPL - HS were significantly different (p <0.05) with C (an average of 39%). Levels of N and lignin levels of all plant organic matter were equal (P> 0.05), the mean of each were 1.36% and 41.13% respectively. C / N ratio in AF - CK and HS was the average of 52.78% or 58 times higher than AF - KK, AF - KM, and AF - KP, the mean of 31.11% Polyphenolic content of different plant organic matter real (p <0.05) between SPL. The largest polyphenol content of 17.5% is found in organic material of plant AF - CK and SPL - HS, while the organic material of the plants on other land is on average 3,4%. Organic plant material with polyphenol content> 2% will be slow weathered.